The legacy of yangchen ebook Avatar, the last airbender. - Yee, F.C (Chronicles of the Avatar, 2023)
From F. C. Yee, the New York Times bestselling author of Avatar, the Last Airbender: The Rise of Kyoshi and Avatar, the Last Airbender: The Shadow of Kyoshi comes a thrilling chapter in the Chronicles of the Avatar series and a page-turning follow-up to Avatar, the Last Airbender: The Dawn of Yangchen . Common enemies make for strange friends . . . Avatar Yangchen has succeeded in bringing a measure of stability to Bin-Er, but her successes have been limited to a single city, and rumors concerning Unanimity—a weapon capable of total obliteration—have led to increasing tensions among the Four Nations. Desperate to restore diplomacy, Yangchen attempts to de-escalate hostilities between heads of state. But in the wake of a brutal assassination and the freeing of Unanimity, Yangchen is forced to bring Kavik—the trusted former companion whose betrayal crushed her—back into her fold. As the Four Nations teeter on the brink of conflict and she begins to unravel the power-hungry Zongdu Chaisee's true agenda, Yangchen is forced to measure the worth of humanity and how much can be sacrificed in the name of balance. Avatar, the Last Airbender: The Legacy of Yangchen , the taut and provocative fourth installment in the Chronicles of the Avatar series, follows Avatar Yangchen as she charts the course of her legacy, finally making peace with her choices and facing Avatarhood with the courage it demands.